Activation of gene expression by double-stranded RNA - Corey, David (Henry Stewart Talks, 2010)
RNA-mediated recognition of chromosomal DNA, Gene silencing, Gene activation, Mechanism of recognition of promoter DNA sequences by duplex RNAs, Recognition of sequences beyond the 3'-termini of genes by duplex RNAs
Archived at 2016/04/17